Model Matematika Persediaan Barang karena Adanya Kerusakan dengan Tingkat Permintaan Eksponensial dan Partial Backlogging - Iswarnedi Iswarnedi; Muhammad Subhan; Riry Sriningsih (Journal of Mathematics UNP, 2021)
Abstract – Inventory control by companies is needed to ensure of customers’s demand. Optimal order quantity is a model that uses for counting the optimal total of an item, which could be bought or produced to minimize the costs, both in terms of supplies and processing order purchase. The purpose of this research is to form the inventory model for deteriorating item with exponential demand rate. The method is descriptive method by analyzing the theories which are relevant to the problem. Finally, we get the model form and numerical example that is given to illustrate the model.Keywords– mathematical model, inventory, exponensialdemandrate,deterioration,partialbacklogging